Complex assessment of eurofit tests for students - Siupsinskas, L.; Vainoras, A.; Zumbakyte, R.; Kajeniene, A. (International Journal of Computer Science in Sport, 2002)
According to the World Health Organization`s definition of health - health is a state of complete physical, mental and social well - being and not merely the absence of disease or infirmity (WHO 1948). We have decided to analyze one component of health - physical state of the human body. There are a lot of methods for the assessment of physical activity and physical capacity. The most widespread method, known in our country for the physical health assessment is European tests of physical fitness - EUROFIT. These tests are sensitive, individual and reliable instruments for assessing various principal dimensions of the human body`s function (cardio - respiratory endurance, strength, muscular endurance and power, flexibility, speed, balance). These tests have number of disadvantages for large epidemiological studies. In order to compare results of certain group of people we have to have reference scales of certain area inhabitants. Research data can`t be compared between different countries too.